2015
DOI: 10.1007/s10164-015-0422-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating behavioral syndromes in coyotes (Canis latrans)

Abstract: As more research focuses on behavioral syndromes and their role in ecological and evolutionary processes, it is imperative that methods to test behavior are valid. The objectives of this study were to (1) assess behavior in captive coyotes (Canis latrans) using three methods [agitation scores, novel object test, and flightinitiation distance (FID)] and (2) to determine whether the three tests were correlated within individuals to describe behavioral syndromes. Female coyotes had higher agitation scores during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 59 publications
(74 reference statements)
1
16
0
Order By: Relevance
“…Social territorial incursions may likely represent a prominent stressor to breeding pairs. Third, previous work has demonstrated consistent individual differences in behavior of the species [68][69][70], providing empirical foundation for the current study. Associations among consistent individual differences in behavior and hormones may suggest that behavioral profiles of the species are hormonally mediated.…”
Section: Introductionsupporting
confidence: 53%
“…Social territorial incursions may likely represent a prominent stressor to breeding pairs. Third, previous work has demonstrated consistent individual differences in behavior of the species [68][69][70], providing empirical foundation for the current study. Associations among consistent individual differences in behavior and hormones may suggest that behavioral profiles of the species are hormonally mediated.…”
Section: Introductionsupporting
confidence: 53%
“…Young et al . 34 used both FID and novel object tests on captive coyotes and recommended both tests would be useful for understanding how bold and exploratory behavior varies across coyote populations. We conducted our work at a rural area (central Utah, USA) and an urban area (Denver, Colorado, USA) and details of each area can be found in Mahoney et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is well‐known that wildlife with accrued experiences of human disturbance over time become increasingly habituated to, and tolerant of, humans (Carrete & Tella, ; Carrete et al, ; Greggor, Clayton, Fulford, & Thornton, ; Perals, Griffin, Bartomeus, & Sol, ; Samia et al, ; Sol et al, ; Vincze et al, ). Moreover, prior work in coyotes has demonstrated that personality differences in risk can be successfully quantified via response to humans (Darrow & Shivik, ; Dawson & Jaeger, ; Gilbert‐Norton, Leaver, & Shivik, ; Murray, Edwards, Abercrombie, & St. Clair, ; Poessel, Gese, & Young, ; Schmidt & Timm, ; Young, Mahe, & Breck, ). The mechanisms that contribute to rapid plasticity in wildlife fear are less well‐understood (Carrete & Tella, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prior work in coyotes has demonstrated that personality differences in risk can be successfully quantified via response to humans (Darrow & Shivik, 2009;Dawson & Jaeger, 2009;Gilbert-Norton, Leaver, & Shivik, 2009;Murray, Edwards, Abercrombie, & St. Clair, 2015;Poessel, Gese, & Young, 2017;Schmidt & Timm, 2007;Young, Mahe, & Breck, 2015). The mechanisms that contribute to rapid plasticity in wildlife fear are less well-understood .…”
Section: Discussionmentioning
confidence: 99%